Residual feed intake and the inclusion of crude glycerin in the diet of feedlot-finished Nellore cattle - Silva, Gabriele Voltareli Da; Batalha, Camila Delveaux Araujo; Cyrillo, Joslaine Noely Dos Santos Gonçalves; Canesin, Roberta Carrilho; Barducci, Robson Sfaciotti [UNESP]; Bonilha, Sarah Figueiredo Martins (CSIRO Publishing, 2022)
Context: The beef market faces an increasing demand for an environmentally friendly production system with high-quality final products. The use of strategies that improve system efficiency without detriment on quality are desired for both producers and consumer. Aims: This study aimed to evaluate the effects of residual feed intake (RFI) and dietary inclusion of crude glycerin on carcass and meat quality traits of feedlot-finished Nellore cattle. Methods: Nellore bulls selected for growth and classified as high (n = 14) and low (n = 14) RFI, with average liveweight of 328 kg and age of 552 days were used. Bulls received a high-concentrate diet for 96 days before slaughter and were randomly allocated to two experimental diets in a 2 × 2 factorial arrangement: RFI class (low or high) and dietary inclusion (CG) or not (WCG) of crude glycerin (20% on dry-matter basis). Data were analysed with the SAS MIXED procedure considering RFI class and diet as fixed effects and selection line as a random effect. Key results: There were no significant differences between RFI classes for dry-matter intake during finishing or production traits. Dry-matter intake tended to be reduced by 16% in CG bulls, without alterations in production. Dietary glycerin inclusion tended to increase the protein content in the Longissimus muscle and significantly reduced the fat content. In low-RFI bulls, shear force was higher in unaged beef, and shear force and myofibrillar fragmentation index tended to be higher in meat aged for 14 days. RFI class did not affect Longissimus muscle fatty acid profile, which was highly influenced by dietary glycerin inclusion. Bulls allocated to the CG treatment had a reduction in saturated fatty acids, an increase in odd-chain fatty acids, and a trend towards increased omega-3 fatty acids, which significantly increased the omega-3:omega-6 ratio. Conclusions: The use of Nellore bulls classified as low-RFI and crude glycerin inclusion in finishing diets of Nellore cattle do not compromise production, carcass traits or beef properties. Implications: This approach increases the efficiency and sustainability of the production process and improves the nutritional characteristics of beef for human consumption.
Keywords: beef cattle; by-products; carcass; cis-vaccenic fatty acid; fatty acid profile; feed efficiency; meat quality